Comparison of Jupyter Interactive Notebook Media and PDF E-Module on Regression Materials for Vocational School Students - Andi Qodrat Munandar; Sukma Ayu; Syamsinar; Taswin Rahmat; Titin Ulang Dari; Wahyu Djuddah (Information Technology Education Journal, 2025)
This study aims to compare the effectiveness of interactive Jupyter Notebook media and PDF-based e-modules in improving vocational high school (SMK) students’ understanding of regression concepts. The research responds to the need for more interactive computational learning environments in teaching statistical modeling, particularly regression, which plays an important role in data analysis and applied mathematics. A quasi-experimental study using a pretest–posttest control group design (INTEC) was conducted with 68 eleventh-grade students. The experimental group (n = 34) learned regression using interactive Jupyter Notebook integrating Python simulations and real-time visualization, while the control group (n = 34) used structured PDF e-modules. Data were collected through a validated 30-item regression concept test (α = 0.88). Statistical analyses included paired and independent sample t-tests and Cohen’s d effect size. The experimental group achieved a significantly higher posttest mean (M = 84.62) than the control group (M = 72.15), with p < 0.001 and a large effect size (d = 1.69), indicating superior conceptual gains. The study was limited to one school and a four-week intervention. The findings support integrating interactive coding environments in vocational regression learning.